DINAMIKA PEMEKARAN KECAMATAN MANDAU DAN KECAMATAN PINGGIR KABUPATEN BENGKALIS TAHUN 2011-2017 - Aisa, Al Haifa Chairu; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Regional expansion in the sense of establishing sub-districts which are designed to spur the formation of new centers of economic growth that will bring growth to increase income and welfare of the community, shorten administrative channels, shorten administrative details, also provide open assistance. The author is interested in discussing the expansion of Mandau and Pinggir subdistricts which were divided into Bathin Solapan and Talang Muandau subdistricts. Mandau District and Pinggir Subdistrict are eligible to be expanded considering these two districts are districts with the largest population and area in Bengkalis Regency. During the pemekaran process, the kecamatan has many obstacles, dynamics during the pemekaran process occurred for six years from 2011 to 2017. There are various deficiencies needed to improve and study during the pemekaran process, Mandau District and Pinggir District. In this study, the writer wants to examine how the dynamics of expansion occur and what are the factors that influence expansion so that Mandau and Pinggir can be expanded. The research method used is a qualitative research method and uses descriptive analysis conducted by conducting interviews. The theory used is regional expansion, regional autonomy and the concept of dynamics. Based on the results of the study found the fact that the dynamics of the division of Mandau District and Pinggir District occurred during the process of expansion from 2011 to inauguration in 2017. The dynamics that occurred quite a lot during 2012 and 2015. The factors that influence this expansion consist of internal factors namely from the Districts of Mandau and Pinggir and external factors originating from the Bengkalis Regency government, Riau Provincial Government and the Central Government. From this research, the writer shows the facts about the changes that occurred in 2011 as the initial year of the proposal for the local government until 2017 which is the year of the inauguration of Mandau Subdistrict which was divided into Bathin Solapan Subdistrict and Pinggir Subdistrict which was expanded as Talang Muandau Subdistrict. Keywords: Dynamics of Expansion, Actors, Regional Autonomy